SAT0312 Incidence of infections in clinical trials of tildrakizumab for moderate to severe chronic plaque psoriasis. (12th June 2018) - Crowley, J.; Leonardi, C.; Sturgill-Koszycki, S.; Menter, A.; Mendelsohn, A.M.; Li, Q.; Cichanowitz, N.; La Rosa, C.
Abstract : Background: Risk of infections is a concern with cytokine inhibitor treatments. Objectives: This analysis assessed infections during phase 2 and 3 trials of tildrakizumab (TIL), a high-affinity, humanised, immunoglobulin G1/κ monoclonal antibody against IL-23p19 under development for moderate to severe chronic plaque psoriasis. Methods: Patients were randomised in P05495 (phase 2; NCT01225731 ), reSURFACE 1 (phase 3; NCT01722331 ), and reSURFACE 2 (phase 3; NCT01729754 ). In Part 1 (Weeks 1–16) of P05495, patients received subcutaneous (SC) TIL 5, 25, 100, or 200 mg or placebo (PBO) at Weeks 0 and 4 and were rerandomized to various TIL doses in Part 2 (Weeks 16–52). In Part 1 (Weeks 1–12) of reSURFACE 1 and 2, patients received SC TIL 200 mg, TIL 100 mg, or PBO at Weeks 0 and 4. Patients were rerandomized in Part 2 (Weeks 12–28) and Part 3 (Weeks 28–64 or –52 in reSURFACE 1 and 2, respectively). Etanercept (ETN) 50 mg was an active control in Parts 1–2 of reSURFACE 2. Treatment-emergent adverse event (AE) data pools (n=2081) for the PBO-controlled and full trial periods (52 weeks for P05495/reSURFACE 2; 64 weeks for reSURFACE 1) were analysed. Severe infections met the regulatory definition of a serious AE or required intravenous antibiotics. Results: In the PBO-controlled period, incidences of infections were comparable for TIL 100 mg and 200 mg (23% and 22%, respectively) and PBO (23%); all were comparable with ETN (24%). Incidences of severe infections were low for all treatment groups (range, 0.0%–0.3%; TIL p≥0.6 vs PBO). In the full trial period, exposure-adjusted rates (patients/100 patient-years) for infections with TIL 100 mg and 200 mg (48.9 and 52.6, respectively) were lower than with PBO and ETN (79.5 and 86.0, respectively). Exposure adjusted rates for severe infections were 1.10, 1.61, 1.96, and 0.91 for TIL 100 mg, TIL 200 mg, ETN, and PBO, respectively. In total, 33 severe infections were identified (respiratory: TIL 100 mg, 4 events; TIL 200 mg, 2 events; ETN and PBO, 0 events; skin: TIL 100 mg, 3 events; TIL 200 mg, 6 events; ETN, 2 events; PBO, 3 events; gastrointestinal: TIL 100 mg, 4 events; TIL 200 mg, 5 events; ETN and PBO, 0 events; urinary tract: TIL 200 mg, 1 event; ETN, 1 event; TIL 100 mg and PBO, 0 events). One patient had bone tuberculosis (TIL 200 mg; original purified protein derivative test was negative); 1 sepsis event (TIL 200 mg) occurred months after ending TIL treatment. Conclusions: Infection rates with TIL treatment were low and comparable to PBO and ETN during the PBO-controlled period. By Weeks 52/64, exposure-adjusted rates remained low for all groups. Acknowledgements: This study was funded by Merck and Co., Inc. Editorial support for abstract submission was provided by Fishawack Communications and funded by Sun Pharmaceutical Industries, Inc. Analyses were presented at the American Academy of Dermatology. Annual Meeting, San Diego, California, USA, 2018 Disclosure of Interest: J. Crowley Grant/research support from: Abbvie, Amgen, Sun Pharma, Lilly, Novartis, Janssen, Regeneron, Sanofi, Merck, Pfizer, Sandoz, MC2 Therapeutics, Verrica, Consultant for: Abbvie, Sun Pharma, Dermira, Lilly, Novartis, Celgene, Speakers bureau: Abbvie, Lilly, Novartis, Regeneron, Sanofi, C. Leonardi Grant/research support from: AbbVie, Actavis, Amgen, Boehringer Ingelheim, Celgene, Coherus, Corrona, Dermira, Janssen, Eli Lilly and Company, Galderma, Janssen, Merck, Novartis, Pfizer, LEO Pharma, Sandoz, Stiefel, UCB, Pfizer, Vitae, and Wyeth, Consultant for: AbbVie, Actavis, Amgen, Boehringer Ingelheim, Celgene, Coherus, Corrona, Dermira, Janssen, Eli Lilly and Company, Galderma, Janssen, Merck, Novartis, Pfizer, LEO Pharma, Sandoz, Stiefel, UCB, Pfizer, Vitae, and Wyeth, Speakers bureau: AbbVie, Actavis, Amgen, Boehringer Ingelheim, Celgene, Coherus, Corrona, Dermira, Janssen, Eli Lilly and Company, Galderma, Janssen, Merck, Novartis, Pfizer, LEO Pharma, Sandoz, Stiefel, UCB, Pfizer, Vitae, and Wyeth, S. Sturgill-Koszycki Employee of: Former employee of Sun Pharmaceutical Industries, Inc., A. Menter Grant/research support from: AbbVie, Allergan, Amgen, Anacor Boehringer Ingelheim, Celgene, Dermira, Eli-Lilly, Galderma, Janssen Biotech, Inc. LEO Pharma, Merck, Neothetics, Novartis, Pfizer, Regeneron, Symbio/Maruho, Xenoport, Consultant for: AbbVie Allergan Amgen Eli-Lilly Galderma Janssen Biotech, Inc LEO Pharma Novartis Pfizer Vitae Xenoport, Speakers bureau: AbbVie, Amgen, Janssen Biotech, Inc LEO Pharma, A. Mendelsohn Employee of: Sun Pharmaceutical Industries, Inc., Q. Li Employee of: Merck Sharp and Dohme Corp., a subsidiary of Merck and Co., Inc., Kenilworth, NJ, USA, N. Cichanowitz Shareholder of: Merck and Co., Inc., Employee of: Merck Sharp and Dohme Corp., a subsidiary of Merck and Co., Inc., Kenilworth, NJ, USA, C. La Rosa Employee of: Merck Sharp and Dohme Corp., a subsidiary of Merck and Co., Inc., Kenilworth, NJ, USA